Audit procedures: analyzing impact of COVID-19 on Rahman Rahman Huq - KPMG Bangladesh - Hossain, Syed Ezat Shahriar (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2024.